PEACE AGREEMENT BETWEEN THE GOVERNMENT OF INDONESIA AND FREE ACEH MOVEMENT: ITS NATURES AND CHALLENGES - Kadir, M. Yakub Aiyub (Indonesia Law Review, 2018)
This paper will assess the progress and challenges of the peace agreement between the Government of Indonesian and Free Aceh Movement (MoU Helsinki) post the enactment of the Law on Aceh Government 11/2006 (LAG), particularly on the vulnerability status of MoU both in national and international legal system. Using normative approach and analysing data from local, national and international sources to describe the recent implementation of MoU. It confirms that after eleven years security and political aspect has been demonstrated, while economic and human rights-related issues remain left behind. Therefore this paper argues that the legalization of MoU in the international procedural system will ensure the compliance of agreement, and strengthen sustainable peace in Aceh-Indonesia context.